CAR-T CELL THERAPY FOR T-CELL MALIGNANCIES - Ugo Testa; Patrizia Chiusolo; Elvira Pelosi; Germana Castelli; Giuseppe Leone (Mediterranean Journal of Hematology and Infectious Diseases)
Chimeric antigen receptor T-cell (CAR-T) therapy has revolutionized the treatment of B-cell lymphoid neoplasia and, in some instances, improved disease outcomes. Thus, six FDA-approved commercial CAR-T cell products that target antigens preferentially expressed on malignant B-cells or plasma cells have been introduced in the therapy of B-cell lymphomas, B-ALLs and multiple myeloma.